Pertanggungjawaban Wali Dalam Menjalankan Kekuasaan Terhadap Harta Anak Di Bawah Umur Setelah Berakhirnya Perwalian - Kartika Gusmawati; Esther Masri; Otih Handayani (Jurnal Hukum Sasana, 2023)
A guardian is a person who is given the authority to carry out a legal act in order to protect the interests of a child who does not have both parents or both parents are incapable of carrying out legal actions. The guardian's responsibility for the person and property of the child under his guardianship until the child is an adult and capable of performing legal actions. The research method that the author uses is normative juridical, namely library research by examining laws and regulations related to legal problems or issues being faced. The results of the author's research that children's assets under guardianship are in the form of permanent objects such as land and buildings and the ownership of land rights is still in the name of the guardian, so when the trust ends or the child is declared an adult the guardian is obliged and responsible for handing over all of the child's assets by transferring rights in the form of grants which must be made a grant deed before the Land Deed Making Officer (PPAT) through the correct legal procedures. Then, the recipient of the grant must arrange the process of transferring land rights to the office of the National Land Agency so that the status of the grant becomes his property.